A diversidade dos Pimplinae (Hymenoptera: Ichneumonidae) na Mata Atlântica, Brasil - Higa, Priscilla Tominaga (Universidade Federal de São Carlos, 2023)
The Pimplinae subfamily is considered one of the oldest in the Ichneumonidae family, consisting of more than 1,700 species in 77 genera around the world. In the Neotropics they are still little known and only about 414 species have been described so far. The need for knowledge about this fauna is emerging in the tropics and many studies involving descriptions of new species, distribution and biology of Pimplinae have been carried out. The objective of this study was to contribute to the knowledge of the Pimplinae fauna with emphasis on the Atlantic Forest (Brazil), a biome that is under constant threat of anthropic occupation. The thesis was divided into three chapters, respectively: Chapter 1. Synthesis of knowledge about the Pimplinae genera that occur in Brazil. We found 19 genera and 87 species belonging to the Ephialtini Tribe and 6 genera and 53 species belonging to the Pimplini Tribe in Brazil. New contributions on the distribution, diagnosis, phylogeny and biology were presented for each genus of Pimplinae. Chapter 2. First inventory of Pimplinae (Hymenoptera: Ichneumonidae) diversity along the latitudinal gradient of the Atlantic Forest. The results showed a trend towards greater species richness of Pimplinae in the tropics than in the subtropics and the low diversity and richness found in the northeast region may be related to greater habitat destruction. Chapter 3. Characterization of the idiobiont and cenobiont faunas of Pimplinae (Hymenoptera: Ichneumonidae) on islands and continental area off the coast of the State of Rio de Janeiro, Brazil. A higher proportion of idiobiont species was found on three islands (Ilha Imboassica, Ilha da Gipóia and at high altitude points on Ilha Grande) and a higher proportion of cenobiont species on two islands (Ilha do Pingo D'água and at two points of low altitude of Ilha Grande). In other places there was the same proportion of wealth of the two strategies. The idiobiont species tended towards greater richness on islands farther from the mainland. Idiobiont specimens of the genus Neotheronia were richer in morphospecies; Pimpla and Zaglyptus were more abundant; among the cenobionts, the genus Zatypota had the highest morphospecies richness; species from other cenobiont genera seem to depend on the availability of local resources. Other considerations relating the Pimplinae fauna found on these islands and on the mainland were presented.
The diversity of Pimplinae (Hymenoptera: Ichneumonidae) in the Atlantic Forest, Brazil
Keywords: Distribuição; Ocorrência; Biodiversidade; Padrão de riqueza; Estratégias; Desenvolvimento; Dinâmica de populações; Biogeografia; Ilhas; Fragmentos; Conservação; Distribution; Occurrence; Biodiversity; Richness pattern; Strategies; Development; Population dynamics; Biogeography; Islands; Fragments; Conservation; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS